Dynamical simulation and load control of a Jeffcott rotor system in Herbst maneuvering flight. (February 2016) - Lei, Hou; Yushu, Chen
In this paper, the dynamical simulation of a nonlinear aircraft rotor system in Herbst maneuvering flight is carried out, though which the load control is discussed for safety purposes. The equations of motion of the system are set up by using Lagrange's equation, in which, the effects of maneuvering flight are formulated by the flight parameters of the aircraft. By employing the method of closest unstable equilibrium point, the stability of periodic solutions for the primary resonance of the system in steady flight is analyzed to demonstrate the existence of double steady solutions in some rotation speed region near the critical speed and the possibility of the switch of them due to the effect of maneuvering flight. By introducing the Herbst flight parameters from the results of a relative control simulation, the dynamical simulation of the system is carried out, from which the switch of the smaller solution of amplitude to the larger solution is observed. Furthermore, the load control is designed by adding a gain λ to the Herbst flight parameters to avoid the switch. Through numerical experiments, it is found that λ = 0.679 is the critical condition of the switch. The results in this paper will provide a better understanding for the effect of aircraft maneuvering flight on the dynamics of the rotor system.